Pengaruh Economic Value Added (EVA) Dan Kinerja Perusahaan Terhadap Market Value Added (MVA) - Dina Supriani; Rieke Pernamasari (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
The added market value of a company can show whether the company's managers have allocated their resources efficiently so that they can provide economic benefits? So that it is often a guide for investors in choosing a company which of course affects the stock price. This study aims to determine the effect of economic value-added, and company performance proxied through return on assets, and debt to equity ratio to market value-added. The population in this study is the LQ 45 index company on the Indonesia Stock Exchange in 2017-2019. Sampling using the purposive sampling method obtained 22 company data studied and the amount of data is 66 data. The results of research using SPSS 22 software show that economic value added, return on assets, and debt to equity ratio has a significant effect on market value-added. So it can be concluded that both added value and historical financial performance have an influence on the amount of company value represented by market value-added.